Manajemen Sumber Daya Manusia Dalam Meningkatkan Kinerja Guru - Luwihta, Aisyah Dana; Fadilah, Nur (PT. Cahya Edupreneur Indonesia, 2023)
Along with the times and technology that is happening in this era of globalization, it has really changed the way of human perspective and demands various aspects of human life to start their activities in new ways and there are actions that are in accordance with the development of this era, and cannot it is undeniable that the education sector must also do the same thing so that it is not out of date. This journal is entitled Management of human resources in improving the performance of Madrasah Aliyah Nurut Taqwa teachers. This research is motivated by the reduced professionalism of teacher performance in carrying out their duties in school institutions, and teaching staff is the most fatal role in achieving the success of the institution. In this journal, researchers use qualitative methods by means of interview, observation, supporting factors include that the head of the madrasa has met managerial competition, supervision, social, good personality and also the madrasah curriculum has local content that is in accordance with the character area. While the inhibiting factors include, there are still teaching staff who have not met the standards and there are still some who have not completed their bachelor’s degree and few teachers are certified.